RAGE Silencing Ameliorates Neuroinflammation by Inhibition of p38-NF-κB Signaling Pathway in Mouse Model of Parkinson’s Disease - Wang, Xiaoli; Sun, Xiaoxuan; Niu, Mengyue; Zhang, Xiaona; Wang, Jing; Zhou, Chang; Xie, Anmu (Frontiers in Neuroscience, 2020)
Accumulating evidence suggested that neuroinflammation played a crucial role in dopaminergic neuronal death in Parkinson’s disease (PD). The receptor for advanced glycation end products (RAGE), a multi-ligand receptor of the immunoglobulin superfamily, has been proposed as a key molecule in the onset and sustainment of the inflammatory response. Engagement of RAGE contributed to neuroinflammation by up-regulating nuclear factor-κB (NF-κB) as well as cytokines. The aim of the present study was to investigate the expression of RAGE in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) treated mice and elucidate the RAGE signal pathway involved in the inflammation. Results showed that RAGE protein and pro-inflammatory cytokines cyclooxygenase 2 (COX-2) were up-regulated in MPTP treated mice. Further experiments showed that RAGE ablation inhibited phosphorylation of IκB and p38 and protected nigral dopaminergic neurons against cell death in the substantia nigra. These results suggested that RAGE participated in the pathogenesis of PD by neuroinflammation and p38MAPK-NFκB signal pathway may be involved in the process. Moreover, interfering with RAGE signaling pathway may be a reasonable therapeutic option in slowing PD development and progression.